An integrated framework for selecting and evaluating the performance of stormwater harvesting options to supplement existing water supply systems. (December 2019) - Dandy, Graeme C.; Marchi, Angela; Maier, Holger R.; Kandulu, John; MacDonald, Darla Hatton; Ganji, Arman
Abstract: Existing water resources are under stress due to increasing demands associated with population and economic growth as well as the effects of climate change which can reduce available supply and increase demand. Alternative sources such as stormwater harvesting and treated wastewater are being considered in many cities to supplement existing water supplies. Stormwater harvesting schemes that supplement existing water supply systems are complex as they consist of an integrated set of components that perform the functions of collection, storage, treatment, distribution and discharge. Many options and possible sizes exist for each component. Furthermore, the selection and evaluation of stormwater harvesting schemes need to consider economic, environmental and social criteria, as well as technical feasibility. In order to deal with this complexity, an integrated framework is presented that assists authorities with determining if stormwater harvesting is preferable to other water sources and, if so, what type of stormwater scheme is best. Highlights: An integrated framework is proposed for the selection and evaluation of supplementary stormwater harvesting schemes. The approach considers economic, environmental and social factors as well as technical feasibility and economic externalities. The framework is applied to a realistic case study of the Parafield stormwater harvesting scheme in South Australia. The case study demonstrates that a number of uses of harvested stormwater may have positive net benefits. Details of cost, energy and greenhouse gas emissions data and calculations are provided for all system components.